The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1161/circulationaha.119.041694
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Sequencing of Mouse Heart Immune Infiltrate in Pressure Overload–Driven Heart Failure Reveals Extent of Immune Activation

Abstract: Background: Inflammation is a key component of cardiac disease, with macrophages and T lymphocytes mediating essential roles in the progression to heart failure. Nonetheless, little insight exists on other immune subsets involved in the cardiotoxic response. Methods: Here, we used single-cell RNA sequencing to map the cardiac immune composition in the standard murine nonischemic, pressure-overload heart failure model. By focusing our anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
207
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 246 publications
(233 citation statements)
references
References 51 publications
8
207
0
1
Order By: Relevance
“…Several studies have demonstrated the implication of OSM in cardiovascular diseases; in fact, its receptor is expressed in cardiomyocytes, which supports these findings. This adipokine is expressed in cardiac tissue from patients undergoing valve surgery, tissues from patients with end-stage heart failure and in aortic samples showing inflammation, but not in healthy hearts [ 186 , 187 , 188 ].…”
Section: Role Of Some Adipokines In Inflammatory Processes Associamentioning
confidence: 99%
“…Several studies have demonstrated the implication of OSM in cardiovascular diseases; in fact, its receptor is expressed in cardiomyocytes, which supports these findings. This adipokine is expressed in cardiac tissue from patients undergoing valve surgery, tissues from patients with end-stage heart failure and in aortic samples showing inflammation, but not in healthy hearts [ 186 , 187 , 188 ].…”
Section: Role Of Some Adipokines In Inflammatory Processes Associamentioning
confidence: 99%
“…Finally, single-cell transcriptome analysis will be crucial to uncovering epigenomic changes within various cellular and sub-cellular populations to further shed light on the correlation of (epi)transcriptomic changes in aged and diseased tissue. Single-cell RNA sequencing of a murine cardiac pressure-overload HF model revealed that induction of HF leads to an intricate immune activation, whereby a myriad of cells, including neutrophils, B cells, NK cells and mast cells are activated [76]. Using this approach, and correlation of aberrant or acute immune responses with disease onset during aging can further shed light onto the underlying mechanisms of the failing heart.…”
Section: Discussionmentioning
confidence: 99%
“…We also performed molecular pathology analysis using cardiac biopsy samples from patients with heart failure before treatment to demonstrate that the level of DNA damage in cardiomyocytes determines clinical prognosis and treatment response [9]. Recent single-cell RNA-seq analysis in heart failure biology has also revealed the involvement of inflammatory cells [10] and the anatomical expression profiles of disease-causing genes [11,12].…”
Section: Single-cell Genomics To Dissect the Biology Of Heart Failurementioning
confidence: 99%